공동주택 지배구조와 입주자 집합행동이 관리비에 미치는 영향 - 조성자; Jo Seoung-ja; 임재만; Lim Jae-man (감정평가학 논집, 2020)
공동주택은 전유공간에 대한 사적 소유권과 공용공간에 대한 집합 소유권이 결합된 유형의 부동산으로, 공용공간은 공동주택단지의 공유자원으로 볼 수 있다. 따라서 본 연구는 공동주택 관리에 입주자, 입주자대표회의, 관리주체 등 다양한 이해관계자가 정보비대칭 상황에서 각자 자신의 효용극대화를 위해 행동한다는 대리인이론(Agency Theory)과 집단 내 개인의 행동을 설명하려는 집합행동이론(Collective Action Theory)에 기초하여 공동주택의 관리비 결정요인을 탐색했다. 본 연구에서 선택한 이론 변수는 관리방식과 세대수, 단지의 이질성, 소유형태 등이다. 연구결과 복도유형, 난방유형, 시설 수 등 물리적 요소가 관리비에 통계적으로 유의한 영향을 미치는 결과를 보였다. 그러나 이론적 예상과 달리 관리방식과 소유형태는 관리비에 유의한 영향을 미치지 않았으며, 세대수와 집단의 이질성은 관리비를 낮추는 영향을 미치는 것으로 나타났다. 그럼에도 이론적 근거에 기초하여 공동주택 관리 문제를 해석하려는 시도에서 본 연구의 의의를 찾을 수 있다. MOH(Multi-Owned Housing) can view as common-pool resources because MOH has the specific characteristics, which individual owners have the exclusive private rights to their units and collective own the common parts with other owners. This study shows the agency theory that various stakeholders, including residents, residents' representatives, and management entities, act on the purpose of maximizing their utility under information asymmetry. This study explored the determinants of the management cost based on the agency theory and collective action theory. In this study, the management mode, ownership type, total units, and group heterogeneity were selected as surrogate variables. As a result, the physical traits(stairway type, heating system, the number of various facilities, etc.) have significant effects on management costs. However, management mode, ownership type do not show significant results. And, the number of total units, and group heterogeneity have the negative effect on management costs. In this study, we can not verify the agent theory and collective action theory in MOH management. But this paper has the insights about the problem of MOH management through the theory-based empirical study.